2021
DOI: 10.3389/fphar.2021.771818
|View full text |Cite
|
Sign up to set email alerts
|

Organic Anion Transporting Polypeptide 2B1 in Human Fetal Membranes: A Novel Gatekeeper for Drug Transport During Pregnancy?

Abstract: Current intervention strategies have not been successful in reducing the risks of adverse pregnancy complications nor maternal and fetal morbidities associated with pregnancy complications. Improving pregnancy and neonatal outcomes requires a better understanding of drug transport mechanisms at the feto-maternal interfaces, specifically the placenta and fetal membrane (FM). The role of several solute carrier uptake transporter proteins (TPs), such as the organic anion transporting polypeptide 2B1 (OATP2B1) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 42 publications
2
11
0
Order By: Relevance
“…61 The recent discovery of multiple drug transporter proteins and drug-metabolizing enzymes in fetal membranes prompted us to speculate that the fetal membrane-decidual interface along with the placenta may also transport drugs. 12,62 To overcome current limitations and to test the potential of a 2nd FMi' to transport drugs, we used two distinct models of the OOCs and tested statin drug transport kinetics, metabolism, and efficacy. Statins were used as a model drug for testing our devices based on our in vitro and in vivo experiences with this drug.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…61 The recent discovery of multiple drug transporter proteins and drug-metabolizing enzymes in fetal membranes prompted us to speculate that the fetal membrane-decidual interface along with the placenta may also transport drugs. 12,62 To overcome current limitations and to test the potential of a 2nd FMi' to transport drugs, we used two distinct models of the OOCs and tested statin drug transport kinetics, metabolism, and efficacy. Statins were used as a model drug for testing our devices based on our in vitro and in vivo experiences with this drug.…”
Section: Discussionmentioning
confidence: 99%
“…Our recent findings have shown the functionally active transporter proteins including phosphoglycoprotein-1, breast cancer receptor protein-1, and organic anion transporter proteins in fetal membranes. 12,13 Current study has shown the protein and gene expression of several active influx and efflux transporters proteins and active cytochrome 3A4 enzyme capable of metabolizing drug molecules, in human fetal membrane cell lines (data in press). Therefore, simultaneous testing of both FMis will be necessary to fully understand the effect of a drug's potential impact during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis suggests that placental changes leading to impaired fetal growth are associated with the development of the acute inflammation of the amnion rather than the fetal inflammatory response, as shown in this study. We cannot fully exclude a contribution of fetal membranes on the production of the chemotactic stimuli along with the placenta for the following reasons: i) transporter proteins in the fetal membranes along with nutritional transport system suggests that fetal membranes play an equal role to that of the placenta in drug and nutrients transports (Ganguly et al, 2021;Kammala et al, 2022); ii) endogenous activities in the fetal membranes on cellular level can generate danger signals (Menon and Peltier, 2020;Sheller-Miller and Menon, 2020;Shahin et al, 2021;Shepherd et al, 2021;Tantengco et al, 2021); iii) fetal membranes function can be independent of the placenta and placental involvement (Menon, 2016); iv) fetal growth restriction can increase apoptosis in the chorionic trophoblast cells of fetal membranes and expression of parathyroid-related protein expression in the fetal membranes (Curtis et al, 2000;Murthi et al, 2005); and v) fetal membranes are not the mere extension of the placenta and have their own identity, function and hence, their compromise alone without the placental involvement can be detrimental (Collins et al, 1993;Menon and Moore, 2020). Therefore, functions of fetal membranes might be impaired in pregnancies complicated by the alteration of fetal growth.…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that many of the SLC transporters are found within the basolateral membrane of placenta, thereby influencing cellular entry at the fetal side of syncytiotrophoblasts. Indeed, immunofluorescence studies have confirmed localization of OCT3, OATP2B1, and OAT4 within the basolateral membrane of syncytiotrophoblasts [ 34 , 35 , 36 , 37 ]. Interestingly, for OATP2B1 and OCT3, there is data also showing their expression in fetal membranes and fetal capillaries, respectively [ 36 , 37 ].…”
Section: Histological and Transport Characteristicsmentioning
confidence: 99%
“…Indeed, immunofluorescence studies have confirmed localization of OCT3, OATP2B1, and OAT4 within the basolateral membrane of syncytiotrophoblasts [ 34 , 35 , 36 , 37 ]. Interestingly, for OATP2B1 and OCT3, there is data also showing their expression in fetal membranes and fetal capillaries, respectively [ 36 , 37 ]. Immunohistochemical and functional analysis have also confirmed preferential localization of the carnitine/organic cation transporter (OCTN2) at the apical membrane of syncytiotrophoblasts [ 38 ].…”
Section: Histological and Transport Characteristicsmentioning
confidence: 99%